Implementation of the Digital Membership System on Customer Loyalty - Ariyanti, Riska; Dailami, D.; Utami, Heriska Fadhilah; Rahmadani, Dinda Sri; Putri, Dwi Fadhilla; Hsb, Adelia Putri; Candra, Nasya Arsyika (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study aims to analyze the implementation of a digital membership system at Sultan Kisaran Barbershop and its impact on customer loyalty. The digital membership system implemented using the WhatsApp Business platform is integrated with the cashier system, allowing customers to monitor point accumulation in real-time and get various attractive incentives. The research method uses a qualitative descriptive approach with data collection through observation, interviews, and transaction documentation. The study's results indicate that implementing a digital system increases the frequency of customer visits, strengthens retention, and triggers referral activities that contribute to the expansion of the customer network. The selection of simple technology that suits local conditions has proven effective in minimizing adaptation barriers, while customer emotional engagement is further strengthened through service personalization. Despite challenges in digital literacy and human resource readiness, training and mentoring efforts have overcome these obstacles. Thematic analysis revealed that the digital membership system provides significant added value in terms of behavior, value perception, and customer emotional attachment, thus supporting a sustainable increase in loyalty.